Sp2 is the only glutamine-rich Specificity protein with minor impact on development and differentiation in myelinating glia. - Wegener, Amelie; Küspert, Melanie; Sock, Elisabeth; Philipsen, Sjaak; Suske, Guntram; Wegner, Michael (Journal of Neurochemistry, 2017)
Oligodendrocytes and Schwann cells are the myelinating glia of the vertebrate nervous system and by generation of myelin sheaths allow rapid saltatory conduction. Previous in vitro work had pointed to a role of the zinc finger containing specificity proteins Sp1 and Sp3 as major regulators of glial differentiation and myelination. Here, we asked whether such a role is also evident in vivo using mice with specific deletions of Sp1 or Sp3 in myelinating glia. We also studied glia-specific conditional Sp2- and constitutive Sp4-deficient mice to include all related glutamine-rich Sp factors into our analysis. Surprisingly, we did not detect developmental Schwann cell abnormalities in any of the mutant mice. Oligodendrocyte development and differentiation was also not fundamentally affected as oligodendrocytes were present in all mouse mutants and retained their ability to differentiate and initiate myelin gene expression. The most severe defect we observed was a 50% reduction in Mbp- and proteolipid protein 1 (Plp1)-positive differentiating oligodendrocytes in Sp2 mutants at birth. Unexpectedly, glial development appeared undisturbed even in the joint absence of Sp1 and Sp3. We conclude that Sp2 has a minor effect on the differentiation of myelinating glia, and that glutamine-rich Sp proteins are not essential regulators of the process. (Figure presented.).
EVALuna2:33488
Keywords: C2H2 zinc-finger proteins; glia; myelin; oligodendrocyte; Schwann cell